Pemberian Pelatihan Dan Motivasi Dalam Rangka Meningkatkan Kinerja Kader Di Desa - Damayanti, Kristya; Widiyastuti, Tetty; Septasari, Dinda Dwi (Jurnal Akunida, 2022)
This study aims to determine the effect of training and motivation on the performance of cadres in Maron village, Srengat district, Blitar district. This type of research uses quantitative descriptive using research instruments and quantitative data analysis. Data was collected by using field studies and literature studies. The population in this study were all existing cadres with a total of 35 respondents and the sample of this study used that population. The data analysis method used in this research is validity test, reliability test and multiple linear regression analysis with t test, F test and coefficient of determination (R^2). The results of this study indicate that simultaneously there is a significant influence between training and incentives on the performance of cadres in Maron Village, Srengat District, Blitar Regency with a calculated F value of 13,000 with a sig of 0.000. The results of this study indicate that there is an influence between the provision of training and motivation on the performance of cadres in the village of Maron, Kec. Srengat Kab. Blitar. The conclusion of this study is that both training and motivation variables have an influence on cadre performance